CALCULATION OF THE PERCENTAGE OF AMORPHOUS MATERIAL USING PXRD PATTERNS - Καντηράνης Ν.; Στέργιου Α.; Φιλιππίδης Α.; Δρακούλης Α. (Bulletin of the Geological Society of Greece, 2004)
Standard mixtures of amorphous material (volcanic glass) and crystalline phase (equally participated montmorillonite, muscovite, heulandite, quartz, and calcite) were prepared at the following weight proportions after weighting: 100-0, 75-25, 50-50, 25-75 and 0-100, respectively. From their XRD patterns and using two different techniques of analysis the percentage of amorphous material was calculated. The pure amorphous and crystalline standard mixtures constituted the mixtures of report. The area of the broad background peak of the amorphous material determined using the analogical technique and its percentage was calculated by comparing the measured area to the area of the 100:0 standard mixture, while with the second technique was appreciated the crystallinity of each standard mixture and from this resulted the percentage of amorphous material. It was found that between the two methods there is a very good identification and their divergence concerning the weighed percentages varied between ±3 wt. %. The percentage proportion of minerals based in the values resulted from the application of mass absorption coefficient is in very good agreement with the weighted proportions. The method of Powder X-Ray Diffraction can constitute a very good tool for the semi-quantitative calculation of the amorphous material contained in a sample.